SCRENING SECARA DINI PENYAKIT CA.CERVIK MELALUI PEMERIKSAAN IVA TES MASA NEW NORMAL COVID-19 PADA WANITA USIA SUBUR DI PERUMAHAN GRAHAELOK PERSADA KEL. KENTEN KAB. BANYUASIN - Desi Hariani; Elvina Indah.S; Era Mardia Sari (LPPM STIKes Mitra Adiguna, 2022)
This study aims to determine the prevalence of cervical precancerous lesions by performing cervical cancer screening through knowledge, attitudes and the IVA test. Methods This study used a descriptive observational study with a cross sectional approach which was conducted on 85 women of childbearing age at Graha Elok Persada Housing Complex, Kel. Kenten Kab. Banyuasin, in mothers aged 20-50 years. The current condition of the Covid-19 pandemic needs special attention, especially in providing optimal health services to the community. The acetic acid visual inspection (IVA) examination is the right method for cervical cancer screening to detect cervical cancer. Based on the results of the chi square test, it is known that the Pearson chi-square value is 0.000 <0.05, so there is a significant relationship between the VIA test and the incidence of cervical cancer using univariate and bivariate analysis.